Hidden tribe: A new species of Stream Toad of the genus Ansonia Stoliczka, 1870 (Anura: Bufonidae) from the poorly explored mountainous borderlands of western Thailand - Chatmongkon Suwannapoom (Pensoft, 2021)
Abstract The integrated results of morphological and molecular phylogenetic analyses confirmed the new species status of a recently discovered population of Ansonia from Suan Phueng District, Ratchaburi Province, Thailand. Ansonia karen sp. nov. is separated from all other species of Ansonia by a unique combination of mensural, discrete morphological, and color pattern characteristics and is the sister species of A. thinthinae from Tanintharyi Division, Myanmar. This discovery fills a geographic hiatus of 350 km between it and A. kraensis from Ranong Province, Thailand. Ansonia karen sp. nov. is the newest member of a long list of range-restricted endemics having been recently discovered in the northern Tenasserim Mountain region of western Thailand and continues to underscore the unexplored nature of this region and its need for conservation.